An Inter-State Comparison of Cardiovascular Risk Factors in Germany: Towards an Explanation of High Ischemic Heart Disease Mortality in Saxony-Anhalt - Stang, Andreas (Deutscher Arzte Verlag, 2014)
BACKGROUND: For years, the state of Saxony-Anhalt has had one of the highest mortality rates from ischemic heart disease among all federal states in Germany. In this article, we provide an overview of the prevalence of known risk factors for ischemic heart disease across the German states and discuss possible artefacts in mortality statistics. METHODS: On the basis of data from a selective literature review and from official statistics, we compare, if available, age-standardized prevalences of diabetes, obesity, increased waist circumference, metabolic syndrome, and cigarette smoking across the German states. We also present statistics on completion of schooling, dropping out of school, and unemployment. RESULTS: Saxony-Anhalt was in first or second place among German states for all of the risk factors considered. It was also among the leaders in the percentage of school dropouts (14.1%), and, in 2011, it had the lowest percentage of persons educated to matriculation level (19.2%). The unemployment rate in Saxony-Anhalt was 11.5% in 2012, one of the highest rates in Germany. Even after unclear and unknown causes of death are taken into account, the high mortality from ischemic heart disease in Saxony-Anhalt (153.3 per 100 000 person years cannot be attributed completely to an artefact. CONCLUSION: The high prevalence of risk factors and the unfavorable profile of social factors are consistent with the observed high mortality from ischemic heart disease in Saxony-Anhalt. There is an urgent need for lasting prevention strategies on all levels—societal, behavioral, and clinical.